D23 The effect of cognitive reserve on age of onset and executive functions in huntington's disease and its neurobiological bases. (13th September 2016) - Garcia-Gorro, Clara; Garau-Rolandi, Maria; Escrichs, Anira; Rodriguez-Dechicha, Nadia; Martinez-Horta, Saül; Vaquer, Irene; Calopa, Matilde; Perez, Jesus; Muñoz, Esteban; Santacruz, Pilar; Ruiz, Jesus M; Mareca, Celia; et al.
Abstract : Background: Although age of onset of Huntington's disease (HD) is mainly determined by the size of the CAG repeat expansion, other factors may play a role. One potential factor is Cognitive Reserve (CR), as it has been shown in other neurodegenerative disorders and ageing. Objective: The objective of this study is to investigate the effect of CR on age of onset in HD and to examine the neural bases underlying the individual differences in executive function that could be due to the effects of CR in HD. Methods: Thirty-one HD patients completed a CR questionnaire and were scanned using functional magnetic resonance imaging. We analysed the Resting State Executive Control Network (RS-ECN), a novel approach to study the brain areas underlying executive function. The strength of connectivity with this network was calculated voxel-wise. The difference between the theoeretical and estimated age of onset (26 symptomatic-HD) was calculated for each patient. Results: Our results revealed that high levels of CR significantly delayed the appearance of clinical symptoms. Functional connectivity and morphometry analysis showed a brain reorganisation modulated by CR, which changed the connectivity strength in the anterior cingulate cortex, in the left superior parietal cortex (SPC) and slowed the volume loss in the bilateral precuneus and the bilateral caudate. Furthermore, higher strength of connectivity in the left SPC was related to better performance in cognitive flexibility (TMT B-A) and working memory (Backward Digits Span) tasks. Conclusions: These findings provide converging evidence that CR might act as a protective mechanism for the progression of the disease, delaying the onset of symptoms and improving the performance in executive functions by modulating the RS-ECN and slowing brain atrophy.